The State of Research on Reading Comprehension in University Students - Quintero Ramirez, Magda Yuliza; Vela Valderrama, Yeraldin (Rastros Rostros, 2016)
Introduction: This article analyzes research from the past five years on the reading comprehension of university students (2009-2014). This research had to contain topics that were recent, innovative, relevant, and based on the identification of tools, strategies, difficulties, and less obvious aspects that contribute to thedevelopment of new knowledge to be used as a tool in the collection of other analyses. Topics such as text comprehension and its processes and characteristics were among those found. All of this was carried out through the line of research of teaching of the Spanish language and literature at the Universidad de la Am-azonia and approved by the Research Committee of the Spanish Language and Literature Program of the Department of Education Sciences.  Methodology: The content of 50 research studies with a focus on methodology, theoretical referents, and trends was analyzed in order to obtain an assessment at the national and international level.  Results: Deficiencies, techniques, and elements related to the processes of reading and understanding in university students were identified.  Conclusions: The research serves as an overview of the current conditions that dominate in the field of reading and indicates a lack of awareness of the reader expectations that students manage to develop in this constant task.
Keywords: reading comprehension; university student; education; training; reading